Methodological bases of the introduction of cloud technologies in educational institutions - Nazira, Ospanova; Gulmira Maratovna, Abildinovaa; AkerkeАkanova; Nurgul, Tokzhigitova; Dinara, Naimanova (Opción, 2019)
The aim of the study is to consider all the possibilities and types of cloud technologies, to apply the methodological basis of their implementation in educational institutions via psychological, pedagogical and methodical literature review. According to the results of the analysis, we can talk about a high degree of familiarity with cloud services, but the level of everyday use of cloud services is not so high. In conclusion, the emerging tasks require new solutions in the creation and updating of the organization of training, the inclusion of the latest technical and technological tools in order to improve efficiency and optimization.